DIRECT AND INDIRECT CORRECTIVE FEEDBACK ON EFL STUDENTS WRITING SKILL - Siti Mei Rahmawati (Journal of English and Education, 2017)
There are some corrective feedbacks teachers can give to students in writing English text, two of them are direct corrective feedback and indirect corrective feedback. This study is conducted to investigate the impact of direct corrective feedback and indirect corrective feedback and which feedback is better to improve EFL students writing skill. The study was conducted at SMN N 4 Bandung. The sample of this study was 38 junior high school students and divided into two groups. Group 1 is the direct corrective feedback group and Group 2 is indirect corrective feedback group. Group 1 and group 2 were treated differently regarding their error in writing short story. Statistical analysis test revealed that indirect corrective feedback was more effective that direct corrective feedback in improving students writing skill.